Anemometer: computer interfacing hardware: article / Ruhaidawati Mohd. Ali Piah - Mohd. Ali Piah, Ruhaidawati (2004)
The development of a computer-interfacing for a Digital-Propeller-Anemometer involves a few sets of instrumentation process. These processes include the process of capturing, transmitting and interfacing the data with a computer, and finally processing the data. The main objective of this paper is to design and build the RS232 terminal using PIC16F873. Hardware to RS232 interfaces for the personal computer or RS232 compatible devices. This routine converts input voltage from the circuit to speed and transmits them afterwards to the target device by using the RS232 transmission protocol. This implementation feature a computer display as visual interface. RS232 data transmission is carried out using a Visual Basic software routine.